Good practices for carrot cultivation - Kodikara, K. M. S.; Senanayake, N. S.; Aheeyar, Mohamed M. M.; Nisansala, Duleesha; Hafeez, Mohsin (International Water Management Institute, 2025)
This technical guide on good practices for carrot cultivation was prepared by the International Water Management Institute (IWMI) in partnership with the Department of Agriculture (DoA), Sri Lanka. The aim is to guide farmers on the good practices for safe and sustainable cultivation.